Food Access, Food Deserts, and the Women, Infants, and Children Program - Qi Wu (Journal of Agricultural and Resource Economics, 2017)
We examine the shopping behavior of Women, Infants, and Children (WIC) Program participants located in food deserts in the Greater Los Angeles area relative to peers in GLA located outside of food-desert boundaries. Results indicate that food-desert participants traveled slightly farther to shop than comparison participants. However, food-desert and non-food-desert participants were equally likely to visit multiple vendors and to visit a supermarket vendor. Food-desert participants did not pay more for program foods relative to comparison participants. On balance, the results indicate that WIC shopping behavior is very similar among food-desert and comparison participants.